2015
DOI: 10.3823/779
|View full text |Cite
|
Sign up to set email alerts
|

Detection and antibiotic resistance pattern of Staphylococcus aureusand (MRSA) isolated from healthcare workers Nares at three Gaza hospitals, Palestine

Abstract: Background: Staphylococcus aureus is a significant cause of nosocomial morbidity and mortality and has been identified as an emerging problem in the community. Here we detect the carriage rate and antibiotic resistance pattern of S. aureus and MRSA isolated from 140 healthcare workers (HCWs) nares at Gaza hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…However, it was higher than the results of studies reported among janitors working in the hospital and non-hospital areas in Mekelle, Ethiopia (17.9%) [10] and Taiwan (15.3%) [14]. The overall prevalence of nasal carriage of MRSA in this study (4.8%) was in agreement with a study conducted in Mekelle, Ethiopia (6.25%) [10]; on the contrary, this nding was lower than the results of the studies conducted in Dessie, Ethiopia (12.7%) [15], Jimma, Ethiopia (8.4%) [12] and Gaza strips, Palestine (22.6%) [16]. But, higher than the results of the studies conducted in Taiwan (2.7%) [14] and Madagascar (1.3%) [17].…”
Section: Discussionsupporting
confidence: 90%
“…However, it was higher than the results of studies reported among janitors working in the hospital and non-hospital areas in Mekelle, Ethiopia (17.9%) [10] and Taiwan (15.3%) [14]. The overall prevalence of nasal carriage of MRSA in this study (4.8%) was in agreement with a study conducted in Mekelle, Ethiopia (6.25%) [10]; on the contrary, this nding was lower than the results of the studies conducted in Dessie, Ethiopia (12.7%) [15], Jimma, Ethiopia (8.4%) [12] and Gaza strips, Palestine (22.6%) [16]. But, higher than the results of the studies conducted in Taiwan (2.7%) [14] and Madagascar (1.3%) [17].…”
Section: Discussionsupporting
confidence: 90%
“…However, it was higher than the results of studies reported among janitors working in the hospital and non-hospital areas in Mekelle, Ethiopia (17.9%) [10] and Taiwan (15.3%) [14]. The overall prevalence of nasal carriage of MRSA in this study (4.8%) was in agreement with a study conducted in Mekelle, Ethiopia (6.25%) [10]; on the contrary, this finding was lower than the results of the studies conducted in Dessie, Ethiopia (12.7%) [15], Jimma, Ethiopia (8.4%) [12] and Gaza strips, Palestine (22.6%) [16]. But, higher than the results of the studies conducted in Taiwan (2.7%) [14] and Madagascar (1.3%) [17].…”
Section: Discussionsupporting
confidence: 89%
“…We think that this zero resistance in this study to glycopeptides and linezolid may be due to its limited prescription and use in Gaza Strip hospitals. So, the full sensitivity to vancomycin, teicoplanin and linezolid can work perfectly against clinical CoNS isolated in Gaza hospitals as indicated against S. aureus in recent reports from Gaza Strip [24,27]. On the other hand, a very low resistance rate was observed to tigecycline and moxifloxacin (3.7% and 8.4% respectively).…”
Section: Discussionmentioning
confidence: 95%
“…High resistance to the aforementioned antibiotics could be mainly due to excessive use, misuse, and great prescription of these medication in Gaza for both hospital and community acquired infections and also in agriculture and animal feeding. Moreover, the lack of an antibiotic policy and the availability of antibiotics sold without a medical doctor prescription in Palestine worsen the case [27]. In view of the high resistance rates of CoNS to these aforementioned antibiotics, treatment of infections caused by CoNS, particularly S. epidermidis and S. haemolyticus at Al Shifa hospital with these antibiotics may not be effective.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation